2017
DOI: 10.1016/j.renene.2017.07.068
|View full text |Cite
|
Sign up to set email alerts
|

Pitch angle control for a small-scale Darrieus vertical axis wind turbine with straight blades (H-Type VAWT)

Abstract: The following served on the Examining Committee for this thesis. The decision of the Examining Committee is by majority vote.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(52 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…For example, Chen et al 87 , using a simple sinusoidal pitch variation demonstrated that the power efficiency was improved significantly (up to ) and that the ripple factor of the power output was correspondingly. Numerical studies conducted by Sagharichi et al 42 demonstrated the variable pitch strategy could lead to an improved turbine power production, which should be applied especially at low and Abdalrahman et al 88 proposed that the application of active pitch control using an intelligent neural network would provide an appropriate technique.…”
Section: Figure Definition Of Blade Pitch Angle 5 261 Active Pitch mentioning
confidence: 99%
“…For example, Chen et al 87 , using a simple sinusoidal pitch variation demonstrated that the power efficiency was improved significantly (up to ) and that the ripple factor of the power output was correspondingly. Numerical studies conducted by Sagharichi et al 42 demonstrated the variable pitch strategy could lead to an improved turbine power production, which should be applied especially at low and Abdalrahman et al 88 proposed that the application of active pitch control using an intelligent neural network would provide an appropriate technique.…”
Section: Figure Definition Of Blade Pitch Angle 5 261 Active Pitch mentioning
confidence: 99%
“…Where Tm is the mechanical torque of the turbine (N.m). To optimize the mechanical efficiency at different wind speeds, there is only one appropriate rotor speed with maximum Cp value and optimum tip speed ratio [28,29].…”
Section: Vawt Modelmentioning
confidence: 99%
“…The authors showed that by decreasing the amplitude of the change in pitch amplitude from 30 + to 8 + , a peak power coefficient greater than 0.3 can be achieved and maintained between peak speed ratios of 1e2.5. Abdalrahman et al [18] studied the effects of fixed and variable pitch blades on the performance of a Darrieus turbine using CFD simulation. A 2D simulation of unsteady flow with a moving mesh and k À u turbulence model.…”
Section: Review Analysismentioning
confidence: 99%